Beyond body size: muscle biochemistry and body shape explain ontogenetic variation of anti-predatory behaviour in the lizard Salvator merianae - Barros, Fabio Cury de; Carvalho, Jose Eduardo de; Abe, Augusto Shinya [UNESP]; Kohlsdorf, Tiana (Company Of Biologists Ltd, 2016)
Anti-predatory behaviour evolves under the strong action of natural selection because the success of individuals avoiding predation essentially defines their fitness. Choice of anti-predatory strategies is defined by prey characteristics as well as environmental temperature. An additional dimension often relegated in this multilevel equation is the ontogenetic component. In the tegu Salvator merianae, adults run away from predators at high temperatures but prefer fighting when it is cold, whereas juveniles exhibit the same flight strategy within a wide thermal range. Here, we integrate physiology and morphology to understand ontogenetic variation in the temperature-dependent shift of anti-predatory behaviour in these lizards. We compiled data for body shape and size, and quantified enzyme activity in hindlimb and head muscles, testing the hypothesis that morphophysiological models explain ontogenetic variation in behavioural associations. Our prediction is that juveniles exhibit body shape and muscle biochemistry that enhance flight strategies. We identified biochemical differences between muscles mainly in the LDH:CS ratio, whereby hindlimb muscles were more glycolytic than the jaw musculature. Juveniles, which often use evasive strategies to avoid predation, have more glycolytic hindlimb muscles and are much smaller when compared with adults 1-2 years old. Ontogenetic differences in body shape were identified but marginally contributed to behavioural variation between juvenile and adult tegus, and variation in anti-predatory behaviour in these lizards resides mainly in associations between body size and muscle biochemistry. Our results are discussed in the ecological context of predator avoidance by individuals differing in body size living at temperature-variable environments, where restrictions imposed by the cold could be compensated by specific phenotypes.
Keywords: Tegu lizards; Morphology; Muscle biochemistry; Behavioural shift; Temperature; Ontogeny; Predation